2014
DOI: 10.4088/pcc.13m01579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic Supplementation on Schizophrenia Symptoms and Association With Gastrointestinal Functioning

Abstract: ClinicalTrials.gov identifier: NCT01242371.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 26 publications
1
121
1
4
Order By: Relevance
“…In response to new information, practicing psychiatrists are beginning to complement traditional treatment approaches with probiotics, herbal medicines, omega-3 fatty acid preparations, b-vitamins and minerals [121]. Dickerson et al (2014) showed that probiotics given once per day improved GI symptoms in individuals with schizophrenia [122].…”
Section: Discussionmentioning
confidence: 99%
“…In response to new information, practicing psychiatrists are beginning to complement traditional treatment approaches with probiotics, herbal medicines, omega-3 fatty acid preparations, b-vitamins and minerals [121]. Dickerson et al (2014) showed that probiotics given once per day improved GI symptoms in individuals with schizophrenia [122].…”
Section: Discussionmentioning
confidence: 99%
“…52 Many of the human studies looked at bowel function, and they did find reduced difficulties in bowel movement, IBS severity, and symptoms in patients. 54,56,58,60 Microbiota analysis helped to confirm that fecal microbiota were altered by probiotic intervention: Lactobacillus was increased and Clostridium decreased by L. plantarum, whereas Bifidobacteria and Lactobacillus were increased by L. casei Shirota. 51,60 More details are shown in Table 2.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Patients with schizophrenia showed no change in PANSS score after treatment with L. rhamnosus for 14 weeks. 54 Patients with rheumatoid arthritis showed no change in anxiety levels, as assessed with the STAI after 8 weeks of L. casei. 55 Three studies conducted in IBS patients all looked into HADS scores before and after interventions, but found no effect of L. casei or fermented milk with L. paracasei and L. acidophilus.…”
Section: Psychiatric Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…126 However, a randomized clinical trial of a probiotic regimen containing Lactobacillus and Bifidobacterium strains failed to show any significant change in the psychiatric outcome measures was observed. 127 Another area in which information is rapidly evolving is that of autism spectrum disorders (ASD). In a study in rodent model, it was found that the composition of gut microbiota in animals with ASD-like behavior is significantly changed compared with control animals.…”
Section: Emerging Areasmentioning
confidence: 99%